The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4ra05850j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of push–pull configuration on the electro-optical and charge transport properties of novel naphtho-difuran derivatives: a DFT study

Abstract: We present a density functional theory (DFT) study pertaining to electro-optical and charge transport properties of two novel derivatives of diphenyl-naphtho[2,1-b:6,5-b 0 ]difuran (DPNDF) as investigated based on push-pull configuration. Both molecular structures of the designed derivatives were optimized, in ground state (S 0 ) as well as excited state (S 1 ), using DFT and time-dependent DFT (TD-DFT) respectively. The push-pull configuration effect was studied meticulously for different electro-optical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 95 publications
(132 reference statements)
0
12
0
Order By: Relevance
“…It has been shown in previous studies that B3LYP is a suitable and consistent functional to calculate the properties of interest for both small and large p-conjugated organic compounds [18][19][20]. In particular, it has reproduced the experimental data for compounds such as azo dyes [21,22], triphenylamine dyes [23], chemosensors [24], phthalocyanines [25], chromene derivatives [26] and oxadiazoles [27].…”
Section: Computational Detailsmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been shown in previous studies that B3LYP is a suitable and consistent functional to calculate the properties of interest for both small and large p-conjugated organic compounds [18][19][20]. In particular, it has reproduced the experimental data for compounds such as azo dyes [21,22], triphenylamine dyes [23], chemosensors [24], phthalocyanines [25], chromene derivatives [26] and oxadiazoles [27].…”
Section: Computational Detailsmentioning
confidence: 67%
“…Yang and co-workers reported that the direct method corresponds to ''the site-energy corrected frontier orbital splitting method'' [39]. Details can be found in the literature [13,14,19,38,41,44,45].…”
Section: Computational Detailsmentioning
confidence: 98%
“…The PBE0/6-31G (d,p) method was applied to calculate the AIP and AEA values of the molecules. The electrostatic surface potentials can also be used to estimate the stability properties of molecules [58][59][60]. Therefore, we calculated the electrostatic surface potentials of molecules at the PBE0/6-31G (d,p) level.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the photostability of organic materials was explained on the basis of MEP [37,41,67]. Recently, we pointed out that greater negative potential distributed on the system would enhance the photostability [40,41,70]. The higher negative electrostatic potential distribution on the surface will make the oxidation more difficult and resist against the degradation of the molecule (due to the oxidation and photoreactions) [37,40,41,67,70].…”
Section: Molecular Electrostatic Potentialsmentioning
confidence: 96%
“…In our earlier study, furan ring with a very low electron reorganization energy λ (e) [36] was analyzed as a good electron transport material. Two furan rings containing DPNDF [25] has been used as parent molecule and the effects of electron withdrawing groups (EWGs) [37,38], heteroatoms substitution [39], push-pull strategy [40] and increasing conjugation [41] were investigated in our previous studies.…”
Section: Introductionmentioning
confidence: 99%